The efficacy of erythropoietin mouthwash in prevention of oral mucositis in patients undergoing autologous hematopoietic SCT: a double‐blind, randomized, placebo‐controlled trial. Issue 1 (27th August 2015) - Hosseinjani, Hesamoddin; Hadjibabaie, Molouk; Gholami, Kheirollah; Javadi, Mohammadreza; Radfar, Mania; Jahangard‐Rafsanjani, Zahra; Hosseinjani, Emadoddin; Shabani, Nazanin; Vaezi, Mohammad; Ghavamzadeh, Ardeshir
Abstract: Oral mucositis (OM) as a complication of high‐dose chemotherapy is frequently occurred in hematopoietic stem cell transplantation (HSCT) settings. Erythropoietin (EPO) has anti‐inflammatory, antioxidant and wound‐healing properties and therefore could have an important role in the prevention of OM. We conducted a double‐blind, randomized, placebo‐controlled trial to evaluate the EPO mouthwash effect on OM incidence and severity in 80 patients with non‐Hodgkin's lymphoma, Hodgkin disease (HD) or multiple myeloma, undergoing autologous hematopoietic stem cell transplantation. Patients received either EPO mouthwash (50 IU/ml, 15 ml four times a day) ( n = 40) or placebo ( n = 40) from the starting day of high‐dose chemotherapy until day +14 after transplantation or until the day of discharge from the hospital, whichever occurred first. OM was evaluated daily for 21 days after transplantation or until resolution of OM according to World Health Organization oral toxicity scale. The incidence of OM (grades 1–4) in the EPO mouthwash group and control group was significantly different (27.5% vs 77.5%, p < 0.001). The mean ± SD of two other parameters of OM including maximum intensity OM score (0.60 ± 1.06 vs 1.67 ± 1.27) and average intensity OM score (0.47 ± 0.80 vs 1.28 ± 0.86) was significantly lower in the intervention group ( p < 0.001). Moreover, the mean ± SD duration of OM was also significantly shorter among the EPO mouthwash recipients (1.92 ± 3.42 days vs 5.42 ± 3.86 days, P < 0.001). Also, the duration of neutropenic fever was significantly shorter in the intervention group (2.12 ± 2.42 days vs 3.95 ± 4.01 days, p = 0.016). It is concluded that EPO mouthwash can reduce the incidence and duration of OM. Copyright © 2015 John Wiley & Sons, Ltd.